Investigating the mechanisms of endometrial cancer risk in polycystic ovary syndrome: can UK biobank help? - Atiomo, William (MedCrave, 2017)
Background: UK biobank was set up to investigate the respective contributions of genetic predisposition and environmental exposure to the development of disease and recruited participants between 2006 and 2010. Our aim was to investigate the feasibility of using UK biobank for exploring the association between polycystic ovarian syndrome (PCOS) and endometrial cancer, including the role played by serum IGF-1 levels.